2022
DOI: 10.1016/j.mtbio.2021.100194
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory functions of human mesenchymal stromal cells are enhanced when cultured on HEP/COL multilayers supplemented with interferon-gamma

Abstract: Human mesenchymal stromal cells (hMSCs) are multipotent cells that have been proposed for cell therapies due to their immunosuppressive capacity that can be enhanced in the presence of interferon-gamma (IFN-γ). In this study, multilayers of heparin (HEP) and collagen (COL) (HEP/COL) were used as a bioactive surface to enhance the immunomodulatory activity of hMSCs using soluble IFN-γ. Multilayers were formed, via layer-by-layer assembly, varying the final layer between COL and HEP and supplemented with IFN-γ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 72 publications
(102 reference statements)
3
15
0
Order By: Relevance
“…After 3 days of cell culture, the control group containing IFN-γ showed a considerable increase in the concentration of all the analytes except for IL-6 compared to the negative control. These results demonstrate, in agreement with recent work by Garcia et al, that the presence of IFN-γ produces a favorable effect on hMSC protein expression . This increase in Z -value by the control group was surpassed by the test groups containing IFN-γ immobilized with PCN-333 and showed a direct correlation between the concentration of MOF and the resulting Z -value, indicating that the presence of MOF in this process was contributing to amplified expression.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…After 3 days of cell culture, the control group containing IFN-γ showed a considerable increase in the concentration of all the analytes except for IL-6 compared to the negative control. These results demonstrate, in agreement with recent work by Garcia et al, that the presence of IFN-γ produces a favorable effect on hMSC protein expression . This increase in Z -value by the control group was surpassed by the test groups containing IFN-γ immobilized with PCN-333 and showed a direct correlation between the concentration of MOF and the resulting Z -value, indicating that the presence of MOF in this process was contributing to amplified expression.…”
Section: Resultssupporting
confidence: 92%
“…hMSCs (10 000 cells/cm 2 ) were seeded on a 96 well-plate, and cell viability was measured after 3 and 6 days of culture with control groups and test groups containing. This viability testing was conducted as we have described in our previous works. Following propagation, the cell culture medium was removed, and 100 μL of solution was added per well containing 90% fresh cell medium and 10% PrestoBlue reagent. The plate was then incubated for 3 h, and the fluorescence intensity was measured using a BioTek multi-mode microplate reader (model Synergy 2) with excitation/emission of 560/590 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[32,61] To investigate the potential of our substrates to influence hMSC immunomodulatory behavior, we cultured cells with and without IFN-γ, since it is a cytokine known to stimulate expression of IDO ( Figure 3A ). [35,36,61,62] First, metabolic activity was assessed via MTT assay after three days of culture. hMSCs were seeded on each peptoid crosslinked hydrogel with and without IFN-γ supplemented at 50 ng/mL in the cell culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the applicability of this system for modulating cell-ECM interactions, we seeded human mesenchymal stromal cells (hMSCs) on the hydrogels, since these cells are promising for allogenic cell therapies and exhibit immunomodulatory functions that are sensitive to matrix mechanics. [3236] We found that the range of stiffness was sufficient to affect cell morphology, proliferation, and immunomodulatory activity, with softer hydrogels producing more therapeutically potent cells. Altogether, this study highlights a unique way to regulate bulk mechanics using a property that is often overlooked or unachievable in synthetic ECM: molecular rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…[28,[31][32][33][34] Our group has previously demonstrated the capacity of heparin/collagen multilayers deposited on flat surfaces in modulating hMSC response to soluble interferon gamma, improving cell proliferation and cytokine expression. [28,35,36] However, for large-scale manufacturing of hMSCs flat surfaces are undesirable given their small output, and thus suspension based bioreactors are preferred. [37] In suspension-based bioreactors, microcarriers are used as the adhesion surface for cell cultures.…”
Section: Introductionmentioning
confidence: 99%